The function f is such that f(x) = x^2 – 2x + 3 Solve f(x) = 27 (The bottom question in the photo)
Mathematics
studywithliv
Question
The function f is such that f(x) = x^2 – 2x + 3
Solve f(x) = 27
(The bottom question in the photo)
Solve f(x) = 27
(The bottom question in the photo)
2 Answer

1. User Answers jimrgrant1
Answer:
x =  4, x = 6
Stepbystep explanation:
Given
f(x) = x²  2x + 3 and f(x) = 27, then equating the 2 gives
x²  2x + 3 = 27 ( subtract 27 from both sides )
x²  2x  24 = 0 ← in standard form
Consider the factors of the constant term ( 24) which sum to give the coefficient of the x term ( 2)
The factors are  6 and + 4, since
 6 × 4 =  24 and  6 + 4 =  2, thus
(x  6)(x + 4) = 0
Equate each factor to zero and solve for x
x  6 = 0 ⇒ x = 6
x + 4 = 0 ⇒ x =  4

2. User Answers perfectofdream123
f(x)= 27
x^2 2x+3=27
×^2x+327=0
x^2x24=0
(x6)(x4)=0
x6=0 or ×4=0
×=6or ×=4